Contraceptive use among lactating women in Ganta-Afeshum District, Eastern Tigray, Northern Ethiopia, 2015: a cross sectional study - Alem Gebremariam; Hadush Gebremariam (BMC, 2017)
Abstract Background Women who are not exclusively breastfeeding are at risk of pregnancy after four to six weeks of childbirth. Postpartum contraceptive use is crucial to prevent unintended pregnancy, and to have spaced births. The study was conducted to determine the magnitude of modern contraceptive utilization and factors associated with it among lactating women in Ganta-Afeshum district. Methods A community based cross sectional study was conducted among lactating women with children in the age group of six to twelve months. A total of 605 women were included in the study. The study participants were selected using cluster sampling method. Data were collected using structured interviewer administered Tigrigna version questionnaire. Data were analyzed using SPSS version 21. Multivariable logistic regression was used to control the effect of confounders. Results The magnitude of institutional delivery was 96.5%. The mode of delivery of the participants was spontaneous, instrumental and caesarean section, 95.5%, 2.0%, and 2.5%, respectively. The magnitude of modern contraceptive (MC) utilization was 68.1% (95% CI: 64.4-71.8). The contraceptive method mix was dominated by Depo-Provera (58.8%) followed by implants (31.8%). Almost all the study participants had at least one antenatal care (ANC) visit (99.7%) during the pregnancy of their index child. Participants who had radio and those who delivered their recent child by assisted delivery had higher odds of modern contraceptive use. Conclusions The magnitude of contraceptive utilization among lactating mothers in the study area was higher than the national survey reports. However, significant numbers of women are not using contraceptives in their postpartum period, making them at risk of pregnancy. Mode of delivery of the women and having radio at home were significantly associated with the women's contraceptive utilization. Family planning information dissemination using radio in rural settings should be encouraged to increase the uptake of contraceptives in the lactating women.